Pengaruh Kepemimpinan Kepala Sekolah Dan Supervisi Akademik Terhadap Kinerja Guru Sekolah Dasar Di Gugus 2 Kecamatan Mauk Kabupaten Tangerang - Hakim, Marwan (JURNAL MANAJEMEN PENDIDIKAN, 2024)
THE INFLUENCE OF SCHOOL PRINCIPAL LEADERSHIP AND ACADEMIC SUPERVISION ON PRIMARY SCHOOL TEACHER PERFORMANCE IN GUGUS 2 MAUK DISTRICT, TANGERANG REGENCYThis research is motivated by the low ability of teachers to manage learning, which impacts the decline in elementary school student achievement in Cluster 2, Mauk District, Tangerang Regency. This reflects the need for principal leadership in improving teacher performance. This research is an ex post facto type of quantitative research. The research population was 102 elementary school teachers in Cluster 2 Mauk District, with a specified sample of 52 respondents. The research instrument used a questionnaire. The results of the research show that the principal's leadership partially has a significant effect on teacher performance by 20.7%, demonstrated by the opportunity for teachers to increase their knowledge of learning materials and knowledge of information and communication technology in learning, which can improve their ability to prepare teacher administration equipment by paying attention to health. And teacher welfare. Partial academic supervision has the most dominant and significant influence on teacher performance, 75 as shown by the guidance provided by the Principal to each teacher in preparing semester programs and not guiding teachers in planning and implementing remedial programs. The principal's leadership and academic supervision simultaneously significantly affect teacher performance by 98.3%, while the remaining 1.8% is influenced by other variables not examined in this thesis. With the low influence of the head's leadership on teacher performance, it is recommended that the headmaster's leadership pay attention to motivating teacher discipline in obeying the rules and regulations in carrying out teaching duties, instructing teachers to organize the administration of learning tools, and following up on academic supervision of teachers by using appropriate supervision approaches and techniques appropriate.